Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Yelissa Hajlita Dewi; Rizki Andy Bhara Mulyanto; Rima Melati (Jurnal Syntax Transformation, 2021)
To establish high performance and productive human resources, it will need manpower who had ability, skills and experiences on their own field; in addition to a good leadership, high motivation and an adequate work environment for each of employee. The purpose of this study to measure the influence from leadership, motivation, and work environment on worker performance. This study will use qualitative descriptive approach by using library research method which is reviewing and re-analyzing the previous studies that relates on subject of the influence from leadership, motivation, and work environment to worker performance. Data will be collected from literature of previous scientific journal studies, then processed and analyzed by data reduction, data display, and verification. As the result from that analysis, that there is an influence from leadership, motivation, and work environment on worker performance.